Antifungal Activity of Cosmos caudatus Kunth Leaf Ethanol Extract Against Candida albicans - Fitriana, Fitriana; Nuryanti, Siska; Ramadhan, Wahyu Gilang (Journal Microbiology Science, 2025)
Ethanol extract of Kenikir leaves (Cosmos caudatus Kunth) is known to contain bioactive compounds such as flavonoids, tannins, saponins, and phenolics, which exhibit potential antibacterial and antifungal properties. This study aimed to evaluate ycandidiasis. Extraction was performed using maceration with 96% ethanol, yielding an extract with a 10.58% recovery rate. Preliminary screening at 0.1% concentration demonstrated fungal growth inhibition. Subsequent testing of Minimum Inhibitory Concentration (MIC) and Minimum Fungicidal Concentration (MFC) employed the solid dilution technique, revealing both MIC and MFC values at 0.1%. Antifungal activity was further assessed using the agar diffusion method at varying concentrations (2.5%, 5%, and 10%), with ketoconazole as a positive control. The largest inhibition zone (9.22 mm diameter) was observed at 10% concentration. Data were analyzed using one-way ANOVA followed by Tukey’s HSD test, revealing statistically significant differences between 2.5% and 10% concentrations, as well as between 5% and 10%. These findings demonstrate that C. caudatus ethanol extract possesses significant antifungal activity against C. albicans.